“This Cosplay Does Not Really Suit Her” : Identity and Gender in Raven Leilani’s Luster - Riski, Riku (My University, 2025)
Contemporary fiction authors apply various approaches to represent identity and gender in the literary context. Representation influences interpretation and shapes the conceptual meaning of identity and gender. The literary representation thus often reflects the diverse essence of identity and gender that have developed in contemporary society through evolving cultural ideals. Focus on gender roles and identity within fiction is one way to explore these concepts. In this thesis, I examine how American author Raven Leilani applies the subversion of identity to challenge traditional gender roles in her debut novel, Luster (2020). The discussion revolves around the dynamic functions of character relationships in Leilani’s narrative, the subversion of identity as a concept in gendered fiction, and finally, how these elements function and interact in the novel. In Luster, Leilani creates a narrative where each character constructs a sense of self by interacting between the ‘self’ and the ‘other’. The subversion of identity enables this interaction, which the narrative portrays as identifiable performative acts. The acts allow a constructed identity free from cultural ideals and gender expectations, which results in a genderless identity. The subversion of identity reshapes relationship dynamics and challenges traditional gender roles in the narrative. Although Leilani’s approach to gender in Luster is interesting regarding gender inequality, I focus more on identity’s complex and evolving nature to examine how identity can challenge traditional gender roles in a literary context.
Keywords: identity, gender, gender roles, subversion of identity, literature, Raven Leilani